IncHI1 plasmids are epidemic vectors that mediate transmission of tet(X4) in Escherichia coli isolated from China - Zhang, Yan; Zhang, Jie; Cai, Ping; Lu, Yang; Sun, Ruan-Yang; Cao, Meng-Tao; Xu, Xiao-Li; Webber, Mark A.; Jiang, Hong-Xia (Frontiers in Microbiology, 2023)
Introduction This study aimed to investigate the genetic factors promoting widespread Q6 dissemination of tet(X4) between Escherichia coli and to characterize the genetic contexts of tet(X4). Methods We isolated E. coli from feces, water, soil and flies collected across a large-scale chicken farm in China in 2020. Antimicrobial susceptibility testing and PFGE typing were used to identify tigecycline resistance and assess clonal relationships among isolates. Plasmids present and genome sequences were analyzed by conjugation, S1 pulsed-field gel electrophoresis (PFGE), plasmid stability testing and whole-genome sequencing. Results A total of 204 tigecycline-resistant E. coli were isolated from 662 samples. Of these, we identified 165 tet(X4)-carrying E. coli and these strains exhibited a high degree of multidrug resistance. Based on the geographical location distribution of the sampled areas, number of samples in each area and isolation rate of tigecycline-resistant strains and tet(X4)-carrying isolates, 72 tet(X4)-positive isolates were selected for further investigation. Tigecycline resistance was shown to be mobile in 72 isolates and three types of tet(X4)-carrying plasmids were identified, they were IncHI1 (n = 67), IncX1 (n = 3) and pO111-like/IncFIA(HI1) (n = 2). The pO111-like/IncFIA(HI1) is a novel plasmid capable of transferring tet(X4). The transfer efficiency of IncHI1 plasmids was extremely high in most cases and IncHI1 plasmids were stable when transferred into common recipient strains. The genetic structures flanked by IS1, IS26 and ISCR2 containing tet(X4) were complex and varied in different plasmids. Discussion The widespread dissemination of tigecycline-resistant E. coli is a major threat to public health. This data suggests careful use of tetracycline on farms is important to limit spread of resistance to tigecycline. Multiple mobile elements carrying tet(X4) are in circulation with IncHI1 plasmids the dominant vector in this setting.